Metagenomic insights into the microbial community of the Buhera soda pans, Zimbabwe - Ngonidzashe Mangoma; Nerve Zhou; Thembekile Ncube (BMC Microbiology)
Abstract Background Soda pans are unique, natural aquatic environments characterised by elevated salinity and alkalinity, creating a distinctive and often extreme geochemistry. The microbiomes of soda pans are unique, with extremophiles such as halophiles, alkaliphiles and haloalkaliphiles being important. Despite being dominated by mostly unculturable inhabitants, soda pans hold immense biotechnological potential. The application of modern “omics-based” techniques helps us better understand the ecology and true extend of the biotechnological potential of soda pan microbiomes. In this study, we used a shotgun metagenomic approach to determine the microbial diversity and functional profile of previously unexplored soda pans located in Buhera, Eastern Zimbabwe. A combination of titrimetry and inductively coupled plasma optical emission spectroscopy (ICP‒OES) was used to perform physico-chemical analysis of the soda pan water. Results Physicochemical analysis revealed that the Buhera soda pans are highly alkaline, with a pH range of 8.74 to 11.03, moderately saline (2.94 – 7.55 g/L), and have high carbonate (3625 mg/L) and bicarbonate ion (1325 mg/L) alkalinity. High levels of sulphate, phosphate, chloride and fluoride ions were detected. Metagenomic analysis revealed that domain Bacteria dominated the soda pan microbial community, with Pseudomonadota and Bacillota being the dominant phyla. Vibrio was shown to be the predominant genus, followed by Clostridium, Candidatus Brevefilum, Acetoanaerobium, Thioalkalivibrio and Marinilactibacillus. Archaea were also detected, albeit at a low prevalence of 1%. Functional profiling revealed that the Buhera soda pan microbiome is functionally diverse, has hydrolytic-enzyme production potential and is capable of supporting a variety of geochemical cycles. Conclusions The results of this pioneering study showed that despite their extreme alkalinity and moderate salinity, the Buhera soda pans harbour a taxonomically and functionally diverse microbiome dominated by bacteria. Future work will aim towards establishing the full extent of the soda pan’s biotechnological potential, with a particular emphasis on potential enzyme production.